2017
DOI: 10.1007/s10555-017-9682-0
|View full text |Cite
|
Sign up to set email alerts
|

Platelet “first responders” in wound response, cancer, and metastasis

Abstract: Platelets serve as “First Responders” during normal wounding and homeostasis. Arising from bone marrow stem cell lineage megakaryocytes, anucleate platelets can influence inflammation and immune regulation. Biophysically, platelets are optimized due to size and discoid morphology to distribute near vessel walls, monitor vascular integrity and initiate quick responses to vascular lesions. Adhesion receptors linked to a highly reactive filopodia-generating cytoskeleton maximizes their vascular surface contact al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
115
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(124 citation statements)
references
References 241 publications
(243 reference statements)
2
115
1
1
Order By: Relevance
“…Hence, coagulopathy may be found in quite a lot patients with severe pneumonia. In this study, platelet count of COVID group was significantly higher than that of non-COVID group, perhaps due to the reactively increased thrombopoietin following pulmonary inflammation [12], this might mean more severe inflammation reaction and hypercoagulability in COVID group, and platelet count may not be a sensitive marker for coagulopathy of COVID-19.…”
Section: Resultsmentioning
confidence: 56%
“…Hence, coagulopathy may be found in quite a lot patients with severe pneumonia. In this study, platelet count of COVID group was significantly higher than that of non-COVID group, perhaps due to the reactively increased thrombopoietin following pulmonary inflammation [12], this might mean more severe inflammation reaction and hypercoagulability in COVID group, and platelet count may not be a sensitive marker for coagulopathy of COVID-19.…”
Section: Resultsmentioning
confidence: 56%
“…33,34 Platelets are an indicator of tumor activity and angiogenesis, and are associated with tumor growth, invasion, and metastasis by releasing VEGF-integrin cooperative signaling. 35,36 Moreover, lymphocytes are an important component of anticancer immunity and immune surveillance and are associated to prevent the tumor growth and progression. 37,38 Some studies have shown that inflammatory markers and immune-based prognostic indexes were used to evaluate the prognosis of breast cancer, such as NLR, d-NLR, MLR/LMR, and PLR.…”
Section: Discussionmentioning
confidence: 99%
“…Platelets are best known for their role in hemostasis,67 but their function in the immune response is an emerging research area. After antigen exposure, platelets get activated as part of the innate immune response and their activation is mediated by surface TLRs and danger signal lipopolysaccharides 68, 69, 70.…”
Section: Immune System and Its Complexitymentioning
confidence: 99%
“…65,66 Tfregs may also inhibit B cell activity by disrupting the mechanical interaction between T cells and B cells. 66 Feedback and feedforward regulation by platelets Platelets are best known for their role in hemostasis, 67 but their function in the immune response is an emerging research area. After antigen exposure, platelets get activated as part of the innate immune response and their activation is mediated by surface TLRs and danger signal lipopolysaccharides.…”
Section: T Cell Activationmentioning
confidence: 99%